Diseño y construcción de un sistema de captación para la vivienda sostenible con aprovechamiento de aguas pluviales del AEIRNNR. - Ojeda Brito, Galo Virgilio (2015)
This thesis aims to design and build a hydraulic system for a greenhouse with rainwater utilization, applied to the rainfall conditions in the south eastern part of the city of Loja, specifically in the Area of Energy, Industries, and non-Renewable Resources of the University of Loja, Argelia place. First was the collection of information to determine the historical behavior of rainfall of the area registered for a period of 32 years; considering that the standard water resource requires a monitoring of the watershed of the study area for a minimum of 30 years. With the data obtained and collected we could size the system of rainwater that was subsequently implemented to meet the requirements of sustainable housing, thus fulfilling the specific objectives. Based on the hydraulic design, the rainwater collection system to collect a month was built and a water distribution pumping system was installed to cover all areas in need of the house.